2019
DOI: 10.3390/en12142776
|View full text |Cite
|
Sign up to set email alerts
|

Control and Restrictions of a Hybrid Renewable Energy System Connected to the Grid: A Battery and Supercapacitor Storage Case

Abstract: This paper studies a Hybrid Renewable Energy System (HRES) as a reliable source of the power supply in the case of the connection to the grid. The grid connection imposes restrictions to the power delivered and harmonic content on the HRES. This causes the HRES to use multiple control systems and subsystems, as the normalization of the measurements, the current control, active harmonic compensation, synchronization, etc., described in this paper. Particular attention was paid to interactions in the storage sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 50 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Arkhangelski et al 26 have suggested a HRES as reliable source of the power supply in the case of grid connection. The hybrid renewable energy source durability was increased by the consolidation of super‐capacitors and batteries.…”
Section: Recent Research Work: a Brief Reviewmentioning
confidence: 99%
“…Arkhangelski et al 26 have suggested a HRES as reliable source of the power supply in the case of grid connection. The hybrid renewable energy source durability was increased by the consolidation of super‐capacitors and batteries.…”
Section: Recent Research Work: a Brief Reviewmentioning
confidence: 99%
“…With regard to energy storage in SGs and SMGs, in the short term it is common to use batteries [6] or supercapacitors [7]. On the other hand, hydrogen constitutes an energy carrier noted for long-term storage to support renewable energies [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, interface devices for PV systems used in RTNs should be single-stage inverters with buck-boost ability (required for proper maximum power point -MPP-of PV panels) in voltages below those of grids, to avoid needs for additional DC-DC converters [34]. There is a tendency to integrate PV/Wind HRES grids with MPP control algorithms and operation of the inverter using Fuzzy logic based controller, as Amir et al [35] proposed, and Arkhangelski et al [36] reported to control current and improve power quality (PQ). For PQ improvement and stability, however, Muthukumar et al [37] developed a "three-level inverter" architecture that improves the power factor of the developed system [38].…”
Section: Introductionmentioning
confidence: 99%